California shellfish farmers: Perceptions of changing ocean conditions and strategies for adaptive capacity. (15th June 2022) - Ward, Melissa; Spalding, Ana K.; Levine, Arielle; Wolters, Erika Allen
Abstract: Coastal communities along the U.S. West Coast experience a myriad of environmental stressors, including exposure to low pH waters exacerbated by ocean acidification (OA). This can result in ecological and social consequences, making necessary the exploration and support for locally relevant strategies to adapt to OA and other environmental changes. The shellfish aquaculture industry along the West Coast is particularly vulnerable to OA, given the negative effects of low pH on shellfish survival and growth. As such, the social-ecological system exemplified by this industry serves as an opportunity to identify and address strategies for local adaptation. Through interviews conducted with West Coast shellfish farm owners and managers ('growers'), we investigate perceptions of OA and environmental change and identify specific strategies for adaptation. We find that growers are concerned about OA, among many other environmental stressors such as marine pathogens and water temperature. However, growers are often unable to attribute changes in shellfish survival or health to these environmental factors due to a lack of data and the resources and network required to acquire and interpret these data. From these interviews, we identify a list of adaptive strategies growers employ or would like to employ to improve their overall adaptive capacity to multiple stressors (environmental, economic, political), which together, allow farms to weather periods of OA-induced stress more effectively. Very few studies to date have identified specific adaptive strategies derived directly from the communities being impacted. This work therefore fills a gap in the literature on adaptive capacity by amplifying the voices of those on the front lines of climate change and identifying explicit pathways for adaptation. Highlights: Shellfish growers were interviewed about their experiences with environmental change. Growers expressed concerns about multiple observed environmental changes. Growers identified seventeen adaptive strategies. Strategies can be categorized as policy/networking, farm management, and science.